Comparative study on RFID, hotspot and car plate scanning method : for intelligent parking management system - A.Hamid, Isredza Rahmi (2005)
Intelligent Parking lvlanagement System technology that enables l:fficil:nt USl: l1! parking will be increasingly important as a growing population placcs c\w-gro\':ing demands on existing transportation infrastructure. While thc problems of parking shortages are well recognized, the cost of providing additional capacity is frl:qucntly prohibitive. Intelligent Parking lv!anagemcnt System may pro\'idl: a scnsible mC~lns to effectively increase parking capacity, while simultancously rl:ducing lkmand by enabling parking service operators to charge market rates depcnding on timl: of day. The potential benefits of Intelligent Parking lv!anagement System arl: it GlI1 impm"l: security for both car park operators and car park users, flexible acccss contml to easily accommodate visitors and delivery vehicles, imprO\'e traffic flo\\' during pC:lk periods and others. The Intelligent Parking lvlanagement system using Radio Frequency Identification (RFID) and hotspot technology is thl: ad":Inccd p:lrking technologies to manage existing parking spaces at a shopping complex to incrcasl: effective capacity and transit access. Smart parking systems implemcntcd \\,orld\\'idt: have been found to reduce delays and improve convenience of parking (Shahl:cn, 2003). The car plate scanning implement also can reduce vehicle stolen problem and increase the security of parking area more competcntly. Although this is :I nc\\' technology in Malaysia, the RFID application is world \\'idc accl:ptl:d by othl:r country. The research method is a primary data which is gathercd through a litnaturl: review and on line web on RFID, hotspot and car plate scanning mcthod. Through this research, the writer found that passive RFID tags is morc cost cffccti"l: than active tags. It also the Jnost preferable tag by other rescarchcr. Although thl:rc art: some obstacles to implement RFID and hotspot technology, during invcstigation, thl: writer found that there arc four solutions can be put into practicc: implelllt:nt reference tag to amplify the passivc tag signal to havc grl:atcr length of covnagc, utilize hybrid RFID tag design that is protocol-compatiblc with existing Institutt: of Electrical and Electronics Engineers (IEEE) 802.11 or Bluetooth standards as \\'cll as existing Radio Frequency (RF)-tag standards, the arrangement of antcnna and RFID tag and use RFID reader with Wireless Fidelity (Wi-Fi) 802.11 intcrfacc to dctl:ct RFID tag. Finally, the proposed network architecture for thc Intclligl:nt Parking Management System is designed.